(untitled) (International Journal of Technology and Management Research, 2020)
Work in organizations entails an exchange relationship between employees and organization. Apart from the written employment contract, there still exists a set of mutual expectations from the two parties (employer and employee) which remain unwritten and unvoiced and yet drives the behavior of both workers and organizations alike, and this is what is referred to as the psychological contract. Psychological contract refers to the employees’ subjective interpretations and evaluations of their deal with the organization. The aim of this study is to explore the impact of breaches or violations in the psychological contract on the performance of employees. It aims to present two concurrent hypotheses, based on theoretical interaction effects of social exchanges (conceptualized as social exchange relationships, fairness, and job security).Data were collected from a sample of 150 employees from both Public and Private Banks in Ghana. Regression analysis was used to explore the moderating effects of social exchanges on the relationships between psychological contract breach and work performance (operationalized as in- role behaviors and organizational citizenship behaviors).It was found that the negative relationship between psychological contract breach and work performance was moderated by social exchanges, such that the relationship was stronger for employees with high social exchange relationship, perceived organizational support, and job security which means that psychological contract breach will negatively affect employees with higher expectations in social exchanges. Keywords: Breach of contract; Social interaction; Psychological contracts; Job satisfaction